Penerapan Metode Haversine Formula Pada Pencarian Lokasi Fasilitas Kesehatan Terdekat - Rahmi Hidayati; Nurul Mutiah (STMIK Budi Darma, 2022)
Health facilities are places used to provide health services to the community. Types of public health facilities include hospitals, health centers, clinics, doctor's practices and pharmacies. Knowing the location of the nearest health facility is important in an emergency situation. One way to access health facility information quickly and easily is by using an application on a smartphone. This study builds a mobile application to locate the nearest health facility using the haversine formula. The use of the haversine formula allows users to search for the nearest health facility based on the user's current location. The application that was built can also display information in the form of a sequence of the nearest health facilities based on location data and the type of health facility selected. Testing on the functionality of the application interface was carried out using the black box method, and the test results were obtained based on user ratings of 82.38%, which means that the application built is in the very good category in terms of application interface functionality.